Partial breast irradiation with CyberKnife after breast conserving surgery: a pilot study in early breast cancer - Laura Lozza; Laura Fariselli; Marco Sandri; Mario Rampa; Valentina Pinzi; Maria Carmen De Santis; Marzia Franceschini; Giovanna Trecate; Ilaria Maugeri; Luisa Fumagalli; Francesca Bonfantini; Giulia Bianchi; et al. (Radiation Oncology, 2018)
Abstract Background Local recurrences after breast conserving treatment are mainly close to the original tumor site, and as such shorter fractionation strategies focused on and nearest mammary gland, i.e. accelerated partial breast irradiation (APBI), have been developed. Stereotactic APBI has been attempted, although there is little experience using CyberKnife (CK) for early breast cancer. Methods This pilot study was designed to assess the feasibility of CK-APBI on 20 evaluable patients of 29 eligible, followed for 2 years. The primary endpoint was acute/sub-acute toxicity; secondary endpoints were late toxicity and the cosmetic result. Results Mean pathological tumor size was 10.5 mm (±4.3, range 3–18), 8 of these patients were classified as LumA-like, 11 as LumB-like, and 1 as LumB-HER2-enriched. Using CK-APBI with Iris, the treatment time was approximately 60 min (range~ 35 to ~ 120). All patients received 30 Gy in five fractions delivered to the PTV. The median number of beams was 180 (IQR 107–213; range:56–325) with a median PTV isodose prescription of 86.0% (IQR 85.0–88.5; range:82–94). The median PTV was 88.1 cm3 (IQR 63.8–108.6; range:32.3–238.8). The median breast V100 and V50 was 0.6 (IQR 0.1–1.5; range:0–13) and 18.6 (IQR 13.1–21.7; range:7.5–37), respectively. The median PTV minimum dose was 26.2 Gy (IQR 24.7–27.6; range 22.3–29.3). Mild side effects were recorded during the period of observation. Cosmetic evaluations were performed by three observers from the start of radiotherapy up to 2 years. Patients’ evaluation progressively increase from 60% to 85% of excellent rating; this trend was similar to that of external observer. Conclusions These preliminary results showed the safe feasibility of CK-APBI in early breast cancer, with mild acute and late toxicity and very good cosmetic results. Trial registration The present study is registered at Clinicaltrial.gov (NCT02896322). Retrospectively egistered August 4, 2016.